Cost-Effectiveness of Tele-Video-Consultation for the Neuro-Surgical Emergency Management at the General Hospitals in Italy - Kadel, Rajendra; Evans-Lacko, Sara; Tramarin, Andrea; Stopazzolo, Giampaolo (Frontiers in Neuroscience, 2018)
Background: Neuro-surgical emergencies are serious (long-term disability and high mortality) and costly to the national health services. Tele-medicine intervention can facilitate to reduce this gap. Our study aims to evaluate the cost-effectiveness of tele-video-consultation intervention for the management of neuro-surgical emergencies in the general hospitals. Methods: We retrieved health service data from the tele-consultation service, online tele-medicine database portal and hospital patient registry, between January 2009 and December 2012 and evaluated cost-effectiveness of the tele-video-consultation intervention from an Italian national health service perspective. Results: Seventy-five percent of the tele-consultations were completed within 15 minutes and 90% within 30 minutes. The average costs were €2326 in the intervention group and €4173 in the care as usual group. The intervention avoided 73% potential transfer (saving of 139,916 km travel distance during a four-year period). The incremental cost-saving per transfer avoided from the tele-medicine intervention was €365. Conclusions: Tele-medicine intervention could be worth investing from the Italian national health service perspective.